A Novel and Practical Synthesis of Isavuconazonium Sulfate via Anion Exchange Resin - Lei Huang; Yi Zhang; Hua Chen; Wei-Wei Wang; Jian-Qi Li; Yu Liu (Georg Thieme Verlag KG, 2022)
Abstract In this study, an efficient and practical process for the synthesis of isavuconazonium sulfate (compound 1), an antifungal agent, was described. Highlights in the synthesis route are the usage of the ion exchange resin instead of H2SO4 to introduce the HSO4 − anion in the formulation of quaternary ammonium salt (1), and the reaction condition was further optimized to facilitate the scale-up. The overall yield of the process was 57.0% and the high-performance liquid chromatography purity of product was 97.25%, which was higher than that of the reference-listed drug.